From Grunwick to Gate Gourmet: South Asian Women’s Industrial Activism and the Role of Trade Unions - Sundari Anitha; Ruth Pearson; Linda McDowell (Revue Française de Civilisation Britannique)
Through a focus on two examples of industrial militancy by South Asian women workers in the UK that took place thirty years apart – the Grunwick and Gate Gourmet disputes - this article explores the effectiveness of the trade union movement in representing minority ethnic women workers. We examine these two disputes in the context of the changing nature of the labour market and the significant shift in industrial relations legislation between the 1970s and the 2000s. We reflect on what these two disputes indicate about the extent to which the British trade union movement has changed to reflect the priorities and experience of migrant women workers in the UK over the last four decades.